2010
DOI: 10.5909/jbe.2010.15.5.607
|View full text |Cite
|
Sign up to set email alerts
|

Human Factor Research on the Measurement of Subjective Three Dimensional Fatigue

Abstract: The methods developed to measure visual fatigue so far are quite few and lack of validity, and more importantly, they do not figure out the complex properties of the visual fatigue. The purpose of the research was to analyze the factors comprising the visual fatigue and to develop the method to measure it validly. The results are summarized as follows. First, we found that the 3D visual fatigue was comprised of four independent factors (visual stress, eye pain, body pain and image blurring factors). Second, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 12 publications
1
5
0
9
Order By: Relevance
“…In terms of the visual discomfort, it is revealed that watching the 3D display clearly caused more visual discomfort than watching the 2D display, regardless of the viewing distance. These results are consistent with those of previous studies [9,33,38,42,[47][48][49].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In terms of the visual discomfort, it is revealed that watching the 3D display clearly caused more visual discomfort than watching the 2D display, regardless of the viewing distance. These results are consistent with those of previous studies [9,33,38,42,[47][48][49].…”
Section: Discussionsupporting
confidence: 94%
“…The participants who watched the 3D movies wore passive 3D glasses with lenses having circular-polarizing filters. The participants were asked to answer a visual discomfort questionnaire (VDQ) involving 41 symptoms to rate their perceptions of visual fatigue twice [42,43]. The first VDQ was given before participating in the experiment, and the other was given after participation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…시각피로를 유발하는 디스 플레이 요인은 이외에도 왼 쪽 눈에 입력되는 영상이 오른 쪽에도 일부 입력되어 발생하는 크로스톡 요인이 있다 [5] . 디 스플레이 요인 이외에 콘텐츠 요인, 시청자 요인 그리고 시 청환경요인 등이 시각피로 유발요인으로 지목되고 있다 [6] [7] . 시각피로를 유발하는 디스플레이 요인과 시청환경 요인 그리고 시청자 요인 등은 일부 연구가 진행되었으나 [4]- [7] 콘 텐츠 제작 시에 관여하는 3D 카메라로 인한 시각피로에 대 한 연구는 드물다.…”
unclassified
“…또한 2D 콘텐츠를 시청할 때보다 3D 콘텐 츠를 시청할 때에 유의미한 차이를 보이는 시각피로 정도가 많은 연구를 통해 일관되게 보고되고 있다 [10,11,13,14] . 따라서 본 연구는 이러한 점을 고려하여 3D [19] . 이전 연구결과와 일치하게 [7,8,11,13] , 본 연구에서도 …”
unclassified